Aesthetic Anthropology in the Technocene: Epistemology & Nihilism (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
The transformation of nature operated by the technique has given rise to a new epoch, the Technocene. To understand how technology dominates our societies, it is necessary to explore the foundations of modern epistemology. Faced with this nihilistic and technological epoch, an aesthetic anthropology arises as an alternative to establish a new difference capable of compensate the dominance of the technique. Thus, different practices are discovered, languages that do not reduce the world to calculation and measurement; a clearing that allows the recovery of what is properly human in a world that is entering a posthuman era.